Strategy for Improving the Quality of Education in Madrasas through the Integration of Islamic Values ​​in the Era of Digital Transformation - Syahrul Hasibuan; Maralottung Siregar; Ilham Hasibuan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The development of digital transformation has brought about significant changes in the education system, requiring madrasas to improve their quality through the integration of technology and Islamic values ​​to remain relevant to the needs of modern society. This study aims to analyze strategies for improving the quality of education in madrasas through the integration of Islamic values ​​in the era of digital transformation. The study employed a library research approach with descriptive qualitative methods, analyzing various scientific journals, books, Islamic education, and the quality of madrasa education. Data analysis was conducted using content analysis and thematic analysis techniques to identify patterns, concepts, and relationships among previous research findings. The research results show that strategies to improve the quality of madrasa education are implemented through strengthening digital infrastructure, enhancing teachers' digital competencies, developing an Islamic digital-based curriculum, digitizing educational management, and strengthening Islamic digital culture. The integration of Islamic values ​​into digital learning has been proven to improve the quality of learning, learning motivation, digital literacy. This study concludes that digital transformation based on Islamic values ​​is a crucial strategy for holistically improving the quality of madrasa education. Consequently, madrasas need to strengthen educational digitalization policies that align with strengthening students' Islamic character and ethics.